Online Lexical Competition During Spoken Word Recognition and Word Learning in Children and Adults. Issue 5 (24th February 2013) - Henderson, Lisa; Weighall, Anna; Brown, Helen; Gaskell, Gareth
Abstract : Lexical competition that occurs as speech unfolds is a hallmark of adult oral language comprehension crucial to rapid incremental speech processing. This study used pause detection to examine whether lexical competition operates similarly at 7–8 years and tested variables that influence "online" lexical activity in adults. Children ( n = 20) and adults ( n = 17) were slower to detect pauses in familiar words with later uniqueness points. Faster latencies were obtained for words with late uniqueness points in constraining compared with neutral sentences; no such effect was observed for early unique words. Following exposure to novel competitors ("biscal"), children ( n = 18) and adults ( n = 18) showed competition for existing words with early uniqueness points ("biscuit") after 24 hr. Thus, online lexical competition effects are remarkably similar across development.